2023
DOI: 10.3390/cells12182294
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Synthetic Peptides Based on Glucocorticoid-Induced Leucine Zipper (GILZ) Protein for the Treatment of Inflammatory Bowel Diseases (IBDs)

Musetta Paglialunga,
Sara Flamini,
Raffaele Contini
et al.

Abstract: Glucocorticoids (GCs) are commonly used to treat autoimmune and inflammatory diseases, but their clinical effects and long-term use can lead to serious side effects. New drugs that can replace GCs are needed. Glucocorticoid-induced leucine zipper (GILZ) is induced by GCs and mediates many of their anti-inflammatory effects, such as inhibiting the pro-inflammatory molecule NF-κB. The GILZ C-terminal domain (PER region) is responsible for GILZ/p65NF-κB interaction and consequent inhibition of its transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that a variety of agents that have efficacy in IBD are known to inhibit the NF-κB pathway [33,[89][90][91]. These include some peptide-based drugs, such as Cathelicidin-BF, WFNNAGP, LP-5, pep-1, APE, and LL-37-Tα1 [92][93][94][95][96][97]. Immunohistochemical examination of the colon tissue showed that chensinin-1b effectively suppressed the expression of NF-κB p65.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a variety of agents that have efficacy in IBD are known to inhibit the NF-κB pathway [33,[89][90][91]. These include some peptide-based drugs, such as Cathelicidin-BF, WFNNAGP, LP-5, pep-1, APE, and LL-37-Tα1 [92][93][94][95][96][97]. Immunohistochemical examination of the colon tissue showed that chensinin-1b effectively suppressed the expression of NF-κB p65.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly following the characterization of GILZ in immune cells, the consideration of its therapeutic application emerged (22). Selective upregulation of GILZ and the use of recombinant GILZ protein have emerged as promising therapeutic approaches in diseases like inflammatory bowel disease (IBD), rheumatoid arthritis, psoriasis, sepsis, and diabetic retinopathy (2,(23)(24)(25)(26)(27)(28). Leveraging its anti-inflammatory properties, GILZ holds the potential for therapeutic interventions in these conditions.…”
Section: Introductionmentioning
confidence: 99%